Immunosuppression and outcomes of myocarditis patients presenting with ventricular arrhythmias. (25th November 2020) - Peretto, G; Sala, S; De Luca, G; Marcolongo, R; Campochiaro, C; Tresoldi, M; Foppoli, L; Palmisano, A; Esposito, A; De Cobelli, F; Rizzo, S; Thiene, G; et al.
Abstract: Background: Effects of immunosuppressive therapy (IST) on ventricular arrhythmias (VA) have not been reported in immune-mediated biopsy-proven myocarditis patients. Furthermore, myocarditis arrhythmic risk is still unpredictable. The aim of our study was to evaluate effectiveness of IST on VA in myocarditis patients, and stratify their arrhythmic risk, using clinical and diagnostic features, including serum organ-specific anti-heart (AHA) and antiintercalated-disk autoantibodies (AIDA). Methods: From a cohort of 498 consecutive patients, we enrolled 255 cases with biopsy-proven virus-negative myocarditis and evidence of VA (VF, VT, NSVT, and Lown's grade ≥2 PVC) at index hospitalization. Serum AHA and AIDA were detected by a standardised indirect immunofluorescence technique. Whenever accepted and non-contraindicated, IST was started. Controls (IST-) were chosen after 1:1 matching to IST+ cases by age, gender, ethnicity, left ventricular ejection fraction, VA type, and treatment. Prospective follow-up (FU), occurred at defined timepoints. Results: 58 matched patient couples (42±13 y, 67% males, 50% IST+) were analyzed in the main study cohort. Overall, 28 (24%) had VT, and 62 (53%) were discharged with ICD. IST duration was 12±1 months. No patients died and no serious complications from IST occurred. By 24-month FU, major VA occurred in 6 IST+ vs. 10 IST- patients (p=0.420), with no cases of VT following IST termination. As compared to IST- ones, IST+ patients showed a significant reduction in NSVT and PVC burden, as well as an improvement in clinical, laboratory and imaging findings (all p<0.05). Major VA onset and positive AIDA status were independently associated with major VA at FU (HR 14.2, 95% CI 2.9–68.7, and 8.0, 95% CI 2.6–25.2, respectively, both p<0.001). Furthermore, in the whole study population (N=255), IST played as an independent protective factor from major VA (HR 0.3, 95% CI 0.2–0.7, p=0.005) at 38±21 months FU. Conclusions: In immune-mediated virus-negative myocarditis patients presenting with VA, IST is feasible and effective on NSVT and PVC burden, as well as on structural, laboratory and imaging endpoints. Short-term effects are limited on major VA, which were independently associated with major arrhythmic onset and positive AIDA, in keeping with the proposed etiopathogenetic involvement of autoimmunity in virus-negative myocarditis. Funding Acknowledgement: Type of funding source: None